Health Risk Assessment From Heavy Metals Derived From Drinking Water and Rice, and Correlation With CKDu - Kulathunga, Mudalige R. D. L.; Wijayawardena, M. A. Ayanka; Naidu, Ravi; Wimalawansa, Sunil J.; Rahman, Mohammad Mahmudur (Frontiers in Water, 2022)
Rice is the staple food of most Asians, including Sri Lankans. It is cultivated extensively in the dry zonal regions in Sri Lanka such as the Polonnaruwa district, which also has a higher prevalence of people suffering from the chronic kidney disease of unknown aetiology (CKDu). We investigated the concentrations of potentially toxic heavy metal(loid)s in groundwater and raw rice and attempted to study any link between human exposure to these through groundwater and locally produced food, in relation to the prevalence of CKDu. Measures of human health exposure risks included total daily intake, hazard quotient, hazard index, and carcinogenic risk for consumption of groundwater and rice. In well-water, the concentrations of heavy metal(loid)s, cadmium (Cd), arsenic (As), and lead (Pb) were well-below the WHO stipulated allowable standards. Except for Pb, other heavy metal(loid) contents in all rice samples were found to be lower than WHO maximum permissible limits (0.02 mg/kg). Twenty-three per cent (23%) of rice samples analysed exceeded WHO permissible limit for the total daily intake (TDI) of Pb, and analysis of hazard index for Cd, As, and Pb revealed 26% of rice samples could result in a health risk through the consumption of rice in this population. Further, the outcome depicted no carcinogenic risk of Cd, As, and Pb by consuming rice in this study area. We recommended further studies and investigations to minimize or eliminate the risks from Pb exposure to consumers.